2021
DOI: 10.3389/fimmu.2021.648162
|View full text |Cite
|
Sign up to set email alerts
|

Tremella fuciformis Polysaccharides Inhibited Colonic Inflammation in Dextran Sulfate Sodium-Treated Mice via Foxp3+ T Cells, Gut Microbiota, and Bacterial Metabolites

Abstract: Tremella fuciformis is an edible medicinal mushroom, and its polysaccharide components are found to confer various health benefits. This study identified the protective effects of polysaccharides of Tremella fuciformis (TPs) against dextran sulfate sodium (DSS)-induced colitis in mice. High dose of TPs (HTPs) could prevent the colon from shortening, reduce activity of colonic myeloperoxidase and serum diamine oxidase (DAO), decrease the concentration of D-lactate, and alleviate the colonic tissue damage in col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…Here, DSS treatment also changed the composition of the bacteria community in comparison with the control group; we reviewed the literature and found that it is a common phenomenon. [ 7 , 46 , 47 ] It is understandable because DSS may somehow affect the bacteria community, and on the other hand, colitis is always accompanied by microbiota alteration. [ 48 ] The general enterobacteria composition of each sample at the phylum and family level (Figure 5c,d ) was shown by bar chart and heatmap, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Here, DSS treatment also changed the composition of the bacteria community in comparison with the control group; we reviewed the literature and found that it is a common phenomenon. [ 7 , 46 , 47 ] It is understandable because DSS may somehow affect the bacteria community, and on the other hand, colitis is always accompanied by microbiota alteration. [ 48 ] The general enterobacteria composition of each sample at the phylum and family level (Figure 5c,d ) was shown by bar chart and heatmap, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, some investigators revealed that the amount of intestinal beneficial bacteria is associated with the immune function of the host [ 32 ]. For instance, Xu et al (2021) [ 33 ] found that the increased concentrations of serum IgG and IgA were positively correlated with the increased abundance of intestinal Lactobacillus . Furthermore, the by-products produced from bifidobacterial carbohydrate metabolism act as vectors that directly and indirectly trigger the mucosa-associated immune cells to enhance the immune system of the host [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The column was then eluted with distilled water, 50 mM, 150 mM, and 1 M NaCl successively at flow rates of 10 ml/min. After assessment of their hepatoprotective effects, the 50 mM NaCl eluted part was gathered and lyophilized as FVPs for further research ( Xu et al, 2021b ).…”
Section: Methodsmentioning
confidence: 99%
“…The weight-average (Mw) and number-average (Mn) molecular weights of the FVPs were determined via high-performance gel permeation chromatography, as previously described in the literature ( Xu et al, 2021a ). Fourier transform infrared (FT-IR) spectra of the FVPs were captured using an FT-IR microscope (model iN 10, Thermo Nicolet Corp.; Madison, WI, United States) fitted with a liquid nitrogen-cooled mercury-cadmium-telluride detector ( Xu et al, 2021b ).…”
Section: Methodsmentioning
confidence: 99%